Novel Insight Into the Development and Function of Hypopharyngeal Glands in Honey Bees - Ahmad, Saboor; Khan, Shahmshad Ahmed; Khan, Khalid Ali; Li, Jianke (Frontiers in Physiology, 2021)
Hypopharyngeal glands (HGs) are the most important organ of hymenopteran insects and play critical roles for the insect physiology. In honey bees, HGs are paired structures located bilaterally in the head, in front of the brain between compound eyes. Each gland is composed of thousands of two cell units, secretory cell and duct cell in worker bees. To better understand the recent progress made in understanding the structure and function of these glands, we here review the ontogeny of HGs and the factors affecting the morphology, physiology, and molecular basis of the functionality of the glands. We also review the morphogenesis of HGs in the pupal and adult stages, and the secretory role of the glands across the ages for the first time. Furthermore, recent transcriptome, proteome, and phosphoproteome analyses have elucidated the potential mechanisms driving the HGs development and functionality. This adds a comprehensive novel knowledge of the development and physiology of HGs in honey bees over time, which may be helpful for future research investigations.